Legal Protection for Consumers for Nonconformity of Wedding Organizer Services - Syarah Adilla Imon (Universitas Negeri Semarang, 2026)
The wedding organizer (WO) service industry in Indonesia is growing rapidly in line with the high public demand for professional wedding planning. However, the increase in the use of WO services is also accompanied by various legal problems, especially the incompatibility between the promised services and the services actually provided to consumers. This research endeavors to scrutinize the framework of legal protection afforded to consumers regarding the non-conformity of wedding organizer services and the ensuing liability of business actors, utilizing the specific case of Wedding Organizer Ayu Puspita Sejahtera. The methodologies employed comprise normative legal research, integrating a statute approach, a conceptual approach, and a case approach. Legal data utilized encompasses primary sources namely statutes and regulations alongside secondary sources, including academic literature and scientific journals, supplemented by tertiary materials. The empirical findings reveal that consumers aggrieved by the non-conformity of WO services are granted legal safeguards via Law Number 8 of 1999 concerning Consumer Protection (UUPK) and the Civil Code (KUHPerdata). Pursuant to Article 4 of the UUPK, consumers possess an inherent right to receive services aligning with the promised exchange rate, obtain accurate and truthful information, and secure equitable compensation for any losses sustained. The liability of business actors of WO Ayu Puspita Sejahtera can be qualified as a default based on Article 1238 and Article 1243 of the Civil Code, as well as a violation of the obligations of business actors as stipulated in Article 7 and Article 19 of the Civil Code. This study concludes that the sectoral regulatory gap for wedding organizers in Indonesia weakens the legal position of consumers and makes it difficult to prove service non-conformity, so special regulations are needed that regulate the minimum standards of wedding organizer services to provide certainty and legal justice for consumers.